Analysis of the capabilities of the standard electrometry complex for solving urgent problems of well logging - N. L. Mirontsov (Геофизический журнал, 2012)
Special features of geophysical investigation for wellswith structurally complex, anisotropic, with residual oil-saturated zones, "false" and abnormally low resistance collectors were considered. Ineffectiveness of geo-electric parameters recovery for cross-sections containing such objects through the use of a standard complex (lateral-logging, laterolog survey, induction logging) was demonstrated. Taking logging simulation of such cross-sections as an example, the analysis of special features of their investigation was performed. The required value of vertical resolution capacity of hardware system for investigation of such objects was assessed.